John Ziman and post-academic science: consensibility, consensus, and reliability (Scientiae Studia, 2013)
The main objective of this article is to discuss some of the central theses on the work of the physicist and epistemologist John Michael Ziman concerned with the social dimension of science. Ziman supports the thesis that in order to have a better understanding of the recent changes in scientific practice, especially the consequences brought by a new mode of knowledge production, in the last decades, which he names "post-academic", it is necessary a new methodological approach is necessary that includes, not only philosophical aspects, but also sociological and psychological ones. According to Ziman, one of the consequences of the overvaluation of a managerial culture in post academic science is, in the short term, the deflation of the Mertonian ethos and also of the philosophical principles which were historically shared amongst scientists as regulatory ideals; and in the long run, the major consequence of post-academic science would be the reduction of cognitive capacity of science to produce "new maps" of the world. By the analysis of some key-concepts in Ziman's work, such as "consensibility", "consensuality", "public knowledge" and "post-academic science", we aim to make the Brazilian reader acquainted with his conception of science.